Experimental investigation on a 3000 bar fuel injection system for a SCR-free non-road diesel engine. (1st May 2019) - Boccardo, Giulio; Millo, Federico; Piano, Andrea; Arnone, Luigi; Manelli, Stefano; Fagg, Simon; Gatti, Paolo; Herrmann, Olaf Erik; Queck, Dirk; Weber, Jost
Abstract: The upcoming Stage V emissions regulation for Non-Road Heavy Duty Diesel Engines will force OEMs to adopt Diesel Particulate Filters, adding a further degree of complexity to the aftertreatment system, which in several cases already includes specific devices for NOx reduction. Since complex aftertreatment systems can rise packaging problems as well as reliability issues, the authors evaluated the performance of a Stage V compliant engine layout which can avoid dedicated aftertreatment devices for NOx . This engine features a low pressure exhaust gas recirculation system, a two-stage turbocharger and a 3000 bar injection pressure-capable fuel injection system. This paper focus on the experimental assessment of the performance of the fuel injection system, demonstrating how increasing the rail pressure from 2000 to 3000 bar can dramatically improve the NOx -Soot and NOx -Particulate Number trade-off, together with the engine efficiency, without adversely affecting the emission of nanoparticles. In particular, extremely high injection pressures in conjunction with the use of after injection as a soot reduction technique, was found to be capable of achieving a 50% smoke reduction with a more than acceptable engine efficiency degradation.